2021
DOI: 10.1038/s41562-021-01073-0
|View full text |Cite
|
Sign up to set email alerts
|

The representational dynamics of perceived voice emotions evolve from categories to dimensions

Abstract: Long-standing affective science theories conceive the perception of emotional stimuli either as discrete categories (e.g., an angry voice) or continuous dimensional attributes (e.g., an intense and negative vocal emotion). Which position provides a better account is still widely debated. Here, we contrast them to account for acoustics-independent perceptual and cerebral representational geometry of perceived voice emotions. We combined multimodal imaging of the cerebral response to heard vocal stimuli (functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
(65 reference statements)
5
24
0
Order By: Relevance
“…Moreover, the results are congruent with previous studies, proposing the prolonged activation of several processing areas simultaneously for objects (Cichy et al, 2016), emotional voices (Giordano et al, 2021) and facial expressions (Muukkonen et al, 2020). The current study extends these observations to face identity representations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the results are congruent with previous studies, proposing the prolonged activation of several processing areas simultaneously for objects (Cichy et al, 2016), emotional voices (Giordano et al, 2021) and facial expressions (Muukkonen et al, 2020). The current study extends these observations to face identity representations.…”
Section: Discussionsupporting
confidence: 92%
“…By relating multivariate similarity spaces obtained from EEG and fMRI via RSA, we were able to combine the superior temporal resolution of EEG with the precise spatial resolution of fMRI. This cutting-edge analysis method, that has only been used in a hand-full of studies so far, has brought significant advances in understanding the processing of objects (Cichy et al, 2016(Cichy et al, , 2014Cichy and Pantazis, 2017;Hebart et al, 2018), biological motion (Chang et al, 2021) as well as emotions present in voices (Giordano et al, 2021) or faces (Muukkonen et al,2020;Bayer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that broad-to-specific processing structure over time 7 , 13 , 55 because facial signals of dimensional information can predict specific emotion categories, but not vice versa (but see also Giordano et al. 56 for emotion vocalization processing). Broad dimensional information could also be more robust to degradation in the communication channel 57 and serve distal communication.…”
Section: Resultssupporting
confidence: 57%
“…13 These results thus raise the question of how such multiplexed signals are processed-for example, emotion category and dimensional information could be processed separately and asynchronously, with one informing the other (i.e., serving as priors). Our results suggest that broad-to-specific processing structure over time 7,13,55 because facial signals of dimensional information can predict specific emotion categories, but not vice versa (but see also Giordano et al 56 for emotion vocalization processing). Broad dimensional information could also be more robust to degradation in the communication channel 57 and serve distal communication.…”
Section: Discussionsupporting
confidence: 56%
“…Past research in the voice domain has shown that stimuli obtained through morphing between emotions can be reliably recognised by participants (Bestelmeyer et al, 2010;Laukka, 2005). Recently it was also shown that the early brain responses to these type of stimuli reflect categorical perception, while later stages of perception reflect more dimensional perception (Giordano et al, 2021). However, no study has yet investigated the perception of human voices gradually changing in both their emotional expression and sex.…”
Section: Experiments N 3: Rating Of Voicesmentioning
confidence: 99%